A recuperação intensiva do Ensino Fundamental Ciclo II: uma análise da prática pedagógica do professor de matemática - Ambrosio, Ana Cristina da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper reports the results of a Master thesis developed next to the Graduate Program in Education UNESP - Presidente Prudente, linked to the research line Formative Processes and Practices in Education, with the main objective of describing and analyzing the teaching process practiced by mathematics teachers of Intensive Recovery classes of elementary school cycle II, in the state system of Presidente Prudente, with a view to improving student learning, that is, to see how this educational resource has fulfilled the role of collaborate for the student to overcome their difficulties, helping them to actual construction / acquisition of knowledge. The relevance of this problem is based on the institution of the Continued Progression in the state public schools, which provides an educational organization in the form of cycles without failure, which results in classes with students at different levels of knowledge, constituting the recovery as a key mechanism to ensure that the end of the cycle all students achieve better levels of learning. For the research selected five Mathematics teachers of the class's Intensive Recovery 7th year of primary school, working in five different public schools, in which we conduct observation in their classes and then one semi-structured interviews in which teachers justified their practices. We chose a qualitative approach because our main concern was the teaching process, not just the result. We started making a documentary analysis of legislation related to strengthening and rehabilitation of learning in Brazilian public schools, with emphasis on the State of São Paulo, since 1971...

O presente trabalho relatou os resultados de uma pesquisa de mestrado desenvolvida junto ao Programa de Pós-Graduação em Educação da UNESP - Campus de Presidente Prudente, vinculado à linha de pesquisa Práticas e Processos Formativos em Educação, com o principal objetivo de descrever e analisar o processo de ensino praticado pelos professores de Matemática das classes de Recuperação Intensiva do Ensino Fundamental Ciclo II, na rede estadual de Presidente Prudente, tendo em vista a melhoria da aprendizagem dos alunos, ou seja, verificar como este recurso educacional tem cumprido o papel de colaborar para que o aluno supere suas dificuldades, auxiliando-os na efetiva construção/apropriação do conhecimento. A relevância do problema foi fundamentada na instituição da Progressão Continuada na rede pública estadual paulista, que prevê uma organização educacional na forma de ciclos, sem reprovação, o que acarreta classes com alunos em diferentes níveis de conhecimento, constituindo a recuperação como mecanismo essencial para garantir que, ao final do ciclo, todos os alunos alcancem níveis melhores de aprendizado. Para a realização da pesquisa selecionamos cinco professores de Matemática das turmas de Recuperação Intensiva do 7º ano do Ensino Fundamental, atuantes em cinco escolas públicas diferentes, em que realizamos observação em suas aulas e posteriormente uma entrevista semiestruturada na qual os professores justificaram suas práticas. Optamos por uma abordagem qualitativa, pois a nossa maior preocupação foi o processo de ensino, e não apenas o resultado. Iniciamos com uma análise documental da legislação referente ao reforço e à recuperação da aprendizagem nas escolas públicas brasileiras, com ênfase no Estado de São Paulo, desde 1971...
The intensive recovery of basic education cycle II: an analysis of pedagogical practice of the mathematics teacher
Keywords: Educação; Ensino; Matemática - Estudo e ensino; Ensino fundamental; Aprendizagem; Analise de erros (Matematica); Professores - Avaliação; Professores de matematica; Theaching